Combined transcriptome and metabolome reveal glutathione metabolism plays a critical role in resistance to salinity in rice landraces HD961 - Yang, Shan; Liu, Mengshuang; Chu, Na; Chen, Guanxiu; Wang, Panpan; Mo, Junjie; Guo, Haifeng; Xu, Jianghuan; Zhou, Hongkai (Frontiers in Plant Science, 2022)
Rice (Oryza sativa) is one of the most important food crops around the world, which is sensitive to salt stress, especially in the seedling and booting stage. HD961 is a salt-tolerant rice landrace that grows along coastal beaches and has disease and insect pest resistance, salt tolerance, and vigorous growth characteristics. We performed a combined transcriptome and metabolome analysis to clarify salinity resistance mechanisms in cultivar HD961, which has adapted to salinity soil at the early seedling stage. The results showed that the growth and antioxidant capacity of HD961 were stronger than 9311 under salt stress (SS). Transcriptomic analysis showed that a total of 6,145, 3,309, 1,819, and 1,296 differentially expressed genes (DEGs) were identified in the groups of TH60 (control group vs. 60 mM group of HD961 for transcriptome), TH120 (control group vs. 120 mM group of HD961 for transcriptome), T60 (control group vs. 60 mM group of 9311 for transcriptome), and T120 (control group vs. 120 mM group of 9311 for transcriptome), respectively. Starch and sucrose metabolism and phenylpropanoid biosynthesis were shared in the four treatment groups based on a KEGG enrichment analysis of DEGs. In addition, alpha-linolenic acid metabolism, plant hormone signal transduction, plant-pathogen interaction, and fatty acid elongation were specific and significantly different in HD961. A total of 92, 158, 151, and 179 significantly regulated metabolites (SRMs) responded to SS in MH60 (control group vs. 60 mM group of HD961 for metabolome), MH120 (control group vs. 120 mM group of HD961 for metabolome), M60 (control group vs. 60 mM group of 9311 for metabolome), and M120 (control group vs. 120 mM group of 9311 for metabolome), respectively. The KEGG analysis showed that eight common metabolic pathways were identified in the four treatment groups, of which biosynthesis of amino acids was the most significant. Three specific metabolic pathways were identified in the HD961, including glutathione metabolism, ascorbate and aldarate metabolism, and pantothenate and CoA biosynthesis. Integrative analysis between the transcriptome and metabolome showed that glutathione metabolism was specific and significantly affected under SS in HD961. A total of seven SRMs and 48 DEGs and four SRMs and 15 DEGs were identified in the glutathione metabolism pathway in HD961 and 9311, respectively. The Pearson correlation analysis showed a significant correlation between reduced glutathione and 16 genes (12 upregulated and four downregulated genes), suggesting these genes could be candidates as salt-tolerance regulation genes. Collectively, our data show that glutathione metabolism plays a critical role in response to SS in rice. Moreover, the stronger regulative ability of related common genes and metabolites might contribute to salt resistance in HD961.